Gambaran Histopatologi Insang Ikan Mas di Daerah Endemik Koi Herpesvirus (HISTOPATHOGIC FINDINGS OF GILLS OF THE COMMON CARPS IN THE ENDEMIC AREA OF KOI HERPESVIRUS) - Wasito, Raden; Wuryastuti, Hastari; Sutrisno, Bambang (Jurnal Veteriner; Vol 14 No 3 (2013), 2013)
Koi herpesvirus (KHV)  is the cause of  a lethal disease that affects common carp (Cyprinus carpio)  andkoi (Cyprinus carpio koi). Although, it has been reported that common carps could act as carriers for KHV,their histopathologic findings, especially the gills  have not been identified up to now. In the present study,12  normal, healthy looking common carps including their gills were collected from the endemic area ofKHV in  Sleman, Yogyakarta. All fish were necropsied and the gills were collected and fixed in 10% bufferformalin. Then, the gills were processed histopathologically using routine hematoxyline-eosin stain andexamined under the microscope. Histopathologic examination of the gills exhibited an apparent infiltrationof inflammatory cells, especially lymphocytes. The large oval to polygonal basophilic cells containing largeintranuclear inclusion bodies were also identified. Gills epithelial cells show mass hyperplasia and adhesionwith necrotic changes. Thus, results of this study has led to a reasonable conclusion that KHV infection ispresent in the normal, healthy common carps. One possibility is those KHV  are live viruses (carriers forKHV) and might could act as a source of infection is being discussed.
Keywords: Common carp, KHV, hematoxyline-eosin, intranuclear inclusion bodies, Carriers for KHV